Upaya Pencegahan Bullying pada Anak Sekolah Dasar untuk Mewujudkan Lingkungan Belajar yang Aman dan Nyaman - Naila Zahra; Putri Ghani Sukoco; Azahra Syaharani Sukamto; Elina Dewi Oktaviani; Agne Prasiska Maharani; Sri Suwartini (CV. ITTC INDONESIA, 2026)
Bullying and harassment are common dilemmas in the field of education, particularly at the elementary school level, and have the potential to negatively affect students’ growth and development. This phenomenon not only occurs directly within the school environment but has also expanded into digital spaces through cyberbullying, which is becoming increasingly difficult to control. This study aims to examine the causes, forms, impacts, and prevention efforts of bullying among elementary school students.. This study employs a literature review method (library research) by synthesizing various relevant sources, including books, journals, and scientific articles. The data were analyzed using a descriptive qualitative approach through the processes of collecting, reviewing, classifying, and synthesizing information from various sources related to bullying among elementary school children. The findings indicate that bullying is influenced by peer relationships, family conditions, social differences, lack of supervision, and the improper use of technology. The forms of bullying include physical, verbal, social, and cyberbullying. The impacts are experienced not only by victims but also by perpetrators and witnesses, including emotional problems, decreased academic achievement, low self-confidence, difficulties in social interaction, and the development of aggressive behavior. Therefore, bullying prevention requires the involvement of various stakeholders through character education, the cultivation of moral values, strengthened supervision, and increased student awareness of mutual respect in order to create a safe, comfortable, inclusive, and conducive learning environment for students’ development.